Association of Blood Pressure with Fasting Blood Glucose Levels in Northeast China: A Cross-Sectional Study - Yaogai Lv (Nature Portfolio, 2018)
Abstract Hypertension and diabetes mellitus (DM) have become major public health issues, and previous studies have shown that there is an association between hypertension and DM. However, there is a lack of detailed information about this association. This study aimed to explore how different blood pressure (BP) levels were associated with fasting blood glucose (FBG) levels. A cross-sectional survey with adults aged 18 to 79 years was conducted in Jilin Province, China in 2012. Lambda-mu-sigma (LMS) was used to preliminarily explore the associations of BP with FBG. Quantile regression (QR) was performed to identify the specific associations by adjusting for confounding factors. The distributions of systolic blood pressure (SBP) (χ 2 = 710.76, P < 0.001) and diastolic blood pressure (DBP) (χ 2 = 460.20, P < 0.001) were different according to gender. LMS showed that the associations of BP with FBG became stronger when the FBG levels were close to 5.6 mmol/L. QR showed that FBG was positively associated with SBP (P 30 to P 90) and DBP (P 20 to P 90) in males. In females, FBG was positively associated with SBP from only P 85 to P 90. In summary, FBG was positively associated with BP in a gender-dependent manner.